Study on photocatalytic performance of rutile phased TiO2 micro size rods/flowers film towards methyl orange degradation - Abd Hamed, Noor Kamalia (2017)
Pure rutile titanium dioxide (TiO2) film was fabricated at low temperature of l 50°C by hydrothe1mal method. TiO2 film was developed on Fluorine doped tin oxide (FTO) by using titanium butoxide (TBOT) as a precursor, hydrochloric acid (HCI) and deionized (DI) water. The surface morphology of rutile phased TiO2 films were studied by Field Emission Scanning Electron Microscopy (FESEM). X-ray Diffraction (XRD) was used to analyze the structural prope1ty of the films. Energydispersive spectroscopy (EDX) was used to verify the elemental property of the films. The photocatalytic degradation of methyl orange (MO) was observed by using UV-vis spectroscopy. The photocatalytic analysis was conducted to compare the ability of rutile phased TiO2 film and P25 film (commercial TiO2). The pH solution was varied from pH 3 to IO to study the favorable pH of TiO2 film. The MO concentration was varied from 5 to 15 ppm to find the limited reaction of TiO2 film. The optimum amount of HCI concentration was 15.88 mol/L while the optimum amount of TiO2 loading was 0.123 mol/L. The optimize reaction time was obtained at 10 hours. No degradation was observed after IO hours. The result shows, 0.123 mol/L TBOT concentration of 1225 nm/ has the highest degradation of MO. The degradation was up to 65.6 % while P25 film was 8.07 % only. MO degradation became insignificant at high concentration. From the experiments, it was found that the rutile phased TiO2 has the higher photocatalytic activity in lower MO concentration and favorable in acidic environment.